Contract On Online Lend ing Transaction Based On The Rules Of Lending Services Using Information Technology And Maslahah Mursalah - Ihda Nailul ‘Izzati Rohmah (Journal of Islamic Business Law, 2020)
Online loan transactions are borrow money borrowed transactions through an application and can be accessed by anyone and anywhere by utilizing information technology that is done online. However, online lending transactions cause various problems in their use. This is due to the unexplained agreement that the owner of the application inflict losses on the customer. The research was made aimed at knowing the mechanism of Agreement on online loan transactions when viewed from the Rules of Lending Services Using Information Technology and Maslahah Mursalah perspective. This research uses normative research methods with statue approach and conceptual approach. Analyze data by describing the data by word form and used to interpret and interpret the research result data. Based on Financial Services Authority regulations, the contracts contained in the online loans have largely fulfilled the rules listed in chapter IV of article 18 to 20 POJK number 77/POJK. 01/2016. However, the application owner does not explain the sanctions that will be given if the customer violates the agreement. Whereas based on Maslahah Mursalah, Must meet the 5 elements maqashid and do not violate the element. Other than that the parties shall be equally willing to meet the elements of An-Taradin or Rida.